Managing Large Herbivores in Protected Areas - Rob Found (Global Journal of Ecology - Peertechz Publications, 2016)
By nature of their size, grouping behaviour, and central position within most trophic webs, large terrestrial herbivores -- namely ungulates and elephants -- tend to be both keystone and umbrella species. Their proportionately large impacts on ecosystems extend both top-down (i.e. regulation of vegetation), but also bottom up (regulated their predators). For these reasons, as well as their cultural and economic importance to humans around the world, large herbivores are among the most heavily managed species in any region. Large herbivores have historically been managed by the fact that hunting by humans - or an intentional or forced reduction in that hunting - effectively plays its own top-down role of regulating herbivores. Managing large herbivores in protected areas presents a different set of challenges, however, because where human can no longer hunt large herbivores, the role of humans in the ecosystem is changed dramatically. The necessity of regulating both over and under abundant large herbivore populations remains, however, but we are now challenged to affect this management from outside of our former predator-prey relationships. I reviewed the major approaches to managing large herbivores in protected areas, from a historical perspective, through the development of protected areas and conservation ethics, to more modern methods such as wildlife contraception and behavioural modification. I examine each of these methods from a broader perspective that give further consideration to the impacts on species other than the target species. I synthesize these approaches them from the perspective of holistic ecosystem management, where each method acts to replace a part of ecosystem function that has otherwise been lost by the very fact the herbivore population is in a protected area. As the amount of undisturbed habitat for large herbivores decreases worldwide, these iconic species are increasingly confined only to protected areas, making specific strategies for managing their populations even more important.